New Zealand’s Approach to Parallel Imported Goods and the Copyright Amendment Act 1998 - Coull, Matthew J (Victoria University of Wellington Law Review, 1999)
The prohibition against parallel importing has attracted growing international attention, especially given the global trend towards freeing up international trade. This article examines New Zealand’s new statutory provisions relating to parallel importing following the Copyright Amendment Act 1998. This Act legalises parallel importing in New Zealand in given circumstances. This article critically assesses the economic arguments for parallel importing to analyse whether these support the rationale behind the amendment. It then questions whether the potential defects in the preamendment law were sufficiently severe to warrant the fundamental policy reversal effected by the Act, and discusses alternative avenues of reform and whether these are viable in New Zealand. Underlying the discussion is a consideration of whether the same law should apply to all types of goods, and whether New Zealand’s approach should focus more rigorously on the varying characteristics of individual markets.